Harmful phytoplankton diversity and dynamics in an upwelling region (Sagres, SW Portugal) revealed by ribosomal RNA microarray combined with microscopy - Danchenko, Sergei; Fragoso, Bruno; Guillebault, Delphine; Icely, John; Berzano, Marco; Newton, Alice (Harmful algae, 2019)
•Ribosomal 18S/28S rRNA microarray was applied to improve the detection of HAB species.•Microarray was comparable with microscopy in detecting Pseudo-nitzschia spp. and HAB flagellates and dinoflagellates.•Seasonal upwelling induced by northerly winds was found to be the driving force of HAB events.•Pseudo-nitzschia spp. developed with upwelling events, HAB dinoflagellates occurred during upwelling relaxation. The study region in Sagres, SW Portugal, is subject to natural eutrophication of coastal waters by wind-driven upwelling, which stimulates high primary productivity facilitating the recent economic expansion of bivalve aquaculture in the region. However, this economic activity is threatened by harmful algal blooms (HAB) caused by the diatoms Pseudo-nitzschia spp., Dinophysis spp. and other HAB dinoflagellates, all of which can produce toxins, that can induce Amnesic Shellfish Poisoning (ASP), Diarrhetic Shellfish Poisoning (DSP) and Paralytic Shellfish Poisoning (PSP). This study couples traditional microscopy with 18S/28S rRNA microarray to improve the detection of HAB species and investigates the relation between HAB and the specific oceanographic conditions in the region. Good agreement was obtained between microscopy and microarray data for diatoms of genus Pseudo-nitzschia and dinoflagellates Dinophysis spp., Gymnodinium catenatum and raphidophyte Heterosigma akashiwo, with less effective results for Prorocentrum. Microarray provided detection of flagellates Prymnesium spp., Pseudochattonella spp., Chloromorum toxicum and the important HAB dinoflagellates of the genera Alexandrium and Azadinium, with the latter being one of the first records from the study region. Seasonality and upwelling induced by northerly winds were found to be the driving forces of HAB development, with Pseudo-nitzschia spp. causing the risk of ASP during spring and summer upwelling season, and dinoflagellates causing the risk of DSP and PSP during upwelling relaxation, mainly in summer and autumn. The findings were in agreement with the results from toxicity monitoring of shellfish by the Portuguese Institute for Sea and Atmosphere and confirm the suitability of the RNA microarray method for HABs detection and aquaculture management applications.